Change in Tobacco Use Over Time in Urban Indian Youth: The Moderating Role of Socioeconomic Status. (April 2014) - Mathur, Charu; Stigler, Melissa H.; Erickson, Darin J.; Perry, Cheryl L.; Finnegan, Jonn R.; Arora, Monika; Reddy, K. Srinath
This study investigates socioeconomic differences in patterns and trends of tobacco consumption over time among youth in India. Additionally, the distribution of tobacco use risk factors across social class was examined. The data were derived from a longitudinal study of adolescents, Project Mobilizing Youth for Tobacco Related Initiatives. Students in eight private (high socioeconomic status [SES; n = 2, 881) and eight government (lower SES; n = 5, 476) schools in two large cities in India (Delhi and Chennai) were surveyed annually about their tobacco use and related psychosocial risk factors from 2004 to 2006. Results suggest the relationship between SES and tobacco use over time was not consistent. At baseline (in 2004), lower SES was associated with higher prevalence of tobacco use but the relation between SES and tobacco use reversed 2 years later (2006). These findings were mirrored in the distribution of related psychosocial risk factors by SES at baseline (in 2004), and thereafter in 2006. Implications for prevention scientists and future intervention programs are considered.